The Bible's Viewpoint Of Same-Sex Marriage - Jisman Nainggolan (Jurnal Didaskalia, 2020)
This research aims to explain and understand or understand what same sex marriage is, which is against the Bible's principles, and what factors cause such marriage, and what impact it has on society and the church. So this Biblical study discusses Christian marriage and its implications for God's children in order to understand true Christian marriage. For this reason, the research method used is a qualitative method, namely through documentation and literature research. So this research is to contain the Biblical understanding of Christian marriage, as a basis for providing answers to the rise of same-sex marriage in this era of globalization, and to have a better understanding of Christian marriage based on the Bible for Christians, so that Christians will be able and courageous. bringing in the LGBT community, who in fact are the vast majority of perpetrators of same-sex marriage. Often referred to as gender identity disorder, also known as transsexualism is the mental awareness a person has about their gender, about whether they are male or female in which the gender identity of a transsexual is opposite to the gender that is "imposed" on them based on his physical genitals. Male to female transsexual or what is known as homo and lesbi, namely transsexual male to female, has a male body and a female soul. Until now, the presence of LGBT people around us is still not fully accepted. Not infrequently they are treated like miracles who deserve ridicule, ridicule, or other forms of rejection. In fact, it is the resistance and anti-patience of the community that has been able to trigger the aggressive behavior of LGBT people.